2018
DOI: 10.1208/s12248-018-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Inflammatory Vasculature by Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) are cell membrane-derived compartments that regulate physiology and pathology in the body. Naturally secreted EVs have been well studied in their biogenesis and have been exploited in targeted drug delivery. Due to the limitations on production of EVs, nitrogen cavitation has been utilized to efficiently generate EV-like drug delivery systems used in treating inflammatory disorders. In this short review, we will discuss the production and purification of EVs, and we will summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…These nanovesicles are similar to naturally secreted EVs but contain fewer subcellular organelles and nucleic acids. These EVs were loaded with the anti-inflammatory drug piceatannol and dramatically alleviated acute lung inflammation and sepsis induced by lipopolysaccharide [ 161 , 162 ]. Resolvin D2 was also loaded in PMN-EVs to enhance resolution of inflammation in a mouse stroke model system, therefore protecting the brain from damage during ischemic stroke [ 163 ].…”
Section: Neutrophil-derived Evsmentioning
confidence: 99%
“…These nanovesicles are similar to naturally secreted EVs but contain fewer subcellular organelles and nucleic acids. These EVs were loaded with the anti-inflammatory drug piceatannol and dramatically alleviated acute lung inflammation and sepsis induced by lipopolysaccharide [ 161 , 162 ]. Resolvin D2 was also loaded in PMN-EVs to enhance resolution of inflammation in a mouse stroke model system, therefore protecting the brain from damage during ischemic stroke [ 163 ].…”
Section: Neutrophil-derived Evsmentioning
confidence: 99%
“…We recently reported an approach to generate double-layer membrane-derived nanovesicles (DMVs) from bacteria using nitrogen cavitation, and showed that DMVs can be used as a vaccine to combat bacterial infections 35 . Compared to OMVs 36 , DMVs constitute the whole membrane of gram-negative bacteria and contain endogenous cellular targeting ligands, and DMVs are also stable 26 , 35 , 37 . Our nitrogen cavitation method can be used to generate DMVs from any bacteria and is ready to scale up for translation of our technology 27 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have a short-life span due to spontaneous apoptosis 21 which is an advantage over the EVs generated from general cancer cells. Therefore, recent studies employed dHL-60 cells to investigate NDEVs 22 , 23 and found the beneficial effects on inflammatory diseases, such as acute lung injury and stroke 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%